Profil Minat Belajar Matematika Siswa di Masa Pandemi Covid-19 - Delvin Safitri Handriani; Evi Hulukati; Sumarno Ismail (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses the interest profile of mathematics students to find out how the interest profile of learning mathematics students of class VIII Junior High School 1 Limboto in the pandemic covid-19. The method used is the method of descriptive research. The sample used in this study amounted to 60 students who were divided into 30 students as online learning research samples and 30 students became offline learning research samples. The sampling technique used is simple random sampling. The utilization of learning interest data is done using a questionnaire with 5 measuring indicators, namely (1) feeling happy, (2) Interest in learning, (3) attention in learning, (4) involvement in learning, (5) knowledge in learning. The results showed that students of class VIII of State Junior High School 1 Limboto school year 2020/2021 have a high interest in learning mathematics, both students who follow math teaching online and offline.